2021
DOI: 10.3390/ijms22105165
|View full text |Cite
|
Sign up to set email alerts
|

Rac1/Wave2/Arp3 Pathway Mediates Rat Blood-Brain Barrier Dysfunction under Simulated Microgravity Based on Proteomics Strategy

Abstract: The blood-brain barrier (BBB) is critical to maintaining central nervous system (CNS) homeostasis. However, the effects of microgravity (MG) on the BBB remain unclear. This study aimed to investigate the influence of simulated MG (SMG) on the BBB and explore its potential mechanism using a proteomic approach. Rats were tail-suspended to simulate MG for 21 days. SMG could disrupt the BBB, including increased oxidative stress levels, proinflammatory cytokine levels, and permeability, damaged BBB ultrastructure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…Based on our proteomic results regarding AJ and TJ protein determination and F-actin immunofluorescence, it is possible that SZS maintains BBB integrity by regulating cell junctions and the actin cytoskeleton. It has been reported that cytoskeletal reorganization may be regulated by several signaling pathways, including the Ras-related C3 botulinum toxin substrate 1 (Rac1)- Wiskott-Aldrich syndrome protein family member 2 (WAVE2)- actin related protein 2/3 (Arp2/3) pathway 17 . F-actin assembly and small actin driven protrusions, controlled by the Arp2/3 complex, contribute to the regulation of the paracellular permeability of the BBB 18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our proteomic results regarding AJ and TJ protein determination and F-actin immunofluorescence, it is possible that SZS maintains BBB integrity by regulating cell junctions and the actin cytoskeleton. It has been reported that cytoskeletal reorganization may be regulated by several signaling pathways, including the Ras-related C3 botulinum toxin substrate 1 (Rac1)- Wiskott-Aldrich syndrome protein family member 2 (WAVE2)- actin related protein 2/3 (Arp2/3) pathway 17 . F-actin assembly and small actin driven protrusions, controlled by the Arp2/3 complex, contribute to the regulation of the paracellular permeability of the BBB 18 .…”
Section: Resultsmentioning
confidence: 99%
“…The Arp2/3 complex controls actin polymerization by assembling actin monomers (G-actin) into branched actin filament (F-actin) networks and plays an important role in cadherin/catenin complex-mediated endothelial cell–cell adhesion and the formation and maintenance of barrier integrity 31 . The Arp2/3 complex is activated by the WAVE regulatory complex downstream of Rac1 GTPase 17 . The FAK-DOCK180 signaling cascade plays an important role in the activation of Rac1 GTPase 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Many stimuli can act on endothelial permeability such as a high-fat diet and LPS. The permeability of the blood–brain barrier increases in rats exposed to simulated microgravity by tail suspending, and 3-D clinorotation downregulates the protein levels of ZO-1 and occludin in human brain microvascular endothelial cells ( Yan et al, 2021 ). It has been well-established that the activation of the NLRP3 inflammasome is an important initiating mechanism leading to endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…AQP4 levels, which are elevated when the BBB is compromised, are critically involved in the formation and dissolution of cerebral edema (Amiry-Moghaddam et al, 2003;Frydenlund et al, 2006), suggesting a role for BBB dysfunction in the observed behavioral changes. In another rat study, 21 days of tail suspension resulted in inflammatory cellular infiltration and nuclear pyknosis in the cortex (Yan et al, 2021). Transmission electron microscopy demonstrated a widened intercellular space of endothelial cells, swollen pericytes, and unclear mitochondria cristae.…”
Section: Microgravity and The Blood-brain Barriermentioning
confidence: 92%